Cutaneous plasmacytosis and multinucleate cell angiohistiocytoma‐like lesion in a patient with hepatitis B: A fortuitous triad?. (28th May 2019) - Roy, Simon F.; Ghazawi, Feras M.; Tran, Diane; Bouffard, Danielle
Abstract: A 28‐year‐old woman of Chinese descent, with congenital chronic hepatitis B presented with a 7‐year history of erythematous‐brown papules and plaques on her groins, axillae, and forehead. A first skin biopsy showed findings consistent with two concomitant, yet highly uncommon cutaneous diseases. The presence of lymphoid nodules with germinal centers and clustered polyclonal plasma cells was consistent with cutaneous plasmocytosis. Second, a diffuse proliferation of non‐atypical small vessels (CD31+, CD34+, and HHV8−) in a hypercellular stroma peppered with angulated giant cells (CD163+, CD68−) was suggestive of multinucleate cell angiohistiocytoma (MCAH). Interestingly, the second biopsy of a different plaque on the forehead showed only plasmacytosis and the clinical appearance of both plaques and papules alluded to the distinct presence of both concurrent entities. We speculate the immune modulating effects of chronic hepatitis B may have led to a polyclonal plasmacytic proliferation within the dermis. Furthermore, MCAH has been reported in conjunction with other inflammatory skin diseases such as hidradenitis suppurativa and as such we propose that the MCAH lesion in our case may have arisen as a secondary, reactive process to the cutaneous plasmacytosis.